Primary cutaneous lymphomas – diagnostic and therapeutic guidelines of the Polish Dermatological Society - Sokołowska-Wojdyło, Małgorzata; Maj, Joanna; Robak, Ewa; Placek, Waldemar; Wojas-Pelc, Anna; Jankowska-Konsur, Alina; Olek-Hrab, Karolina; Gniadecki, Robert; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2017)
Primary cutaneous lymphomas are a group of rare lymphoproliferative diseases with incompletely understood pathogenesis. They comprise cutaneous T-cell lymphomas, cutaneous B-cell lymphomas and T/NK-cell lymphomas. The aim of the guidelines is to provide physicians with a tool to facilitate the diagnostic and therapeutic process in patients with this group of diseases. The updated recommendations are consistent with the guidelines for haematologists and oncologists, which will enable the unification of diagnostics and therapy conducted by physicians of all specialties. However, it is important to note that therapeutic decisions must be made individually on the basis of the general condition of the patient, history of internal diseases and medicines used, with careful consideration of the potential efficacy and safety profile of the proposed treatment, which may differ from patient to patient.